Analysis of Public Opinion on the Jakarta Metro as a Solution to Congestion in Jakarta - Rochmah, Wachda Yuniar; Aulia, Darlin; Olivia, Tracy; Fransiska, Vagnes Angela (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The Indonesian government has taken various steps to overcome congestion in the city of Jakarta, including efforts to improve existing public transportation and the construction of new transportation systems such as Mass Rapid Transportation (MRT) Jakarta. The development of public transportation, such as the Jakarta MRT, has an effect on the level of satisfaction and social quality of its users, creating perceptions that reflect satisfaction and loyalty. Nowadays, people express their opinions and perceptions about products or services not only directly but also through social media. Therefore, it is important to understand public perceptions regarding the quality of MRT Jakarta services, especially with the existence of e WOM which is spread on social media and can be a determining factor in decisions to use MRT Jakarta services. The data used for this analysis comes from public opinion on Twitter social media in March-April 2019, namely the first month of the release of MRT Jakarta. The data processing method used is Sentiment Analysis with Orange software. The results of this research show that from all the data, there were 1045 positive tweets, 110 negative tweets and 1430 neutral tweets. This shows that opinions regarding MRT Jakarta at the start of its release were dominated by positive and neutral e-WOM, thus depicting public satisfaction with MRT Jakarta as higher than their dissatisfaction.